2015
DOI: 10.1073/pnas.1424408112
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-8 targets the Wingless signaling pathway in the female mosquito fat body to regulate reproductive processes

Abstract: Female mosquitoes require a blood meal for reproduction, and this blood meal provides the underlying mechanism for the spread of many important vector-borne diseases in humans. A deeper understanding of the molecular mechanisms linked to mosquito blood meal processes and reproductive events is of particular importance for devising innovative vector control strategies. We found that the conserved microRNA miR-8 is an essential regulator of mosquito reproductive events. Two strategies to inhibit miR-8 function i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 32 publications
5
85
1
Order By: Relevance
“…Adverse phenotypes caused by miR-309 miRNA depletion were expected to be alleviated after silencing its major target gene. Previously, phenotypic defects resulting from miRNA deletions were successfully rescued after RNAi silencing their main target genes in A. aegypti (16,17). In our rescue experiments, silencing SIX4 was able to significantly recover phenotypic manifestations caused by miR-309 depletion, such as smaller follicle size and significantly reduced egg numbers.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Adverse phenotypes caused by miR-309 miRNA depletion were expected to be alleviated after silencing its major target gene. Previously, phenotypic defects resulting from miRNA deletions were successfully rescued after RNAi silencing their main target genes in A. aegypti (16,17). In our rescue experiments, silencing SIX4 was able to significantly recover phenotypic manifestations caused by miR-309 depletion, such as smaller follicle size and significantly reduced egg numbers.…”
Section: Resultsmentioning
confidence: 60%
“…The mosquitospecific miR-1174 targets serine hydroxymethyltransferase to control blood intake and digestion in the gut and influences egg development (16). Moreover, the conserved miRNA miR-8 regulates the long-range Wingless signaling that is required for secretion of lipophorin and vitellogenin from the fat body in response to blood feeding, affecting deposition of yolk proteins in oocytes and fecundity of female mosquitoes (17).…”
mentioning
confidence: 99%
“…Furthermore, miR-8-3p and miR-275-3p (ranked 11th; Dataset S1) have been shown previously to be critical in the normal progression of Ae. aegypti egg development PBM (29,31).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies illustrated that miR-275, miR-1174, miR-8, and miR-1890 are essential for the normal progression of blood meal digestion and egg development of Ae. aegypti (29)(30)(31)(32). However, our knowledge of the role of miRNAs in posttranscriptional regulation of the FB genes affecting these tissue functions is limited.…”
Section: Significancementioning
confidence: 99%
“…The second highest expression is for miR‐281 with an expression value of 18,063 and might be involved in the development and metamorphosis of T. tabaci as recent studies showed that miR‐281 regulates the expression of ecdysone receptor ( EcR ) isoform B, in Bombyx mori (Jiang et al., 2013). Another interesting microRNA obtained in the current study was miR‐8, and it can target the Wingless signalling pathway to regulate secretion of yolk protein precursors by the female mosquito fat body and accumulation into the developing ovaries (Lucas et al., 2015, http://www.smartscitech.com/index.php/RD/article/view/815). Therefore, it is quite possible that miR‐8 may play a key role in the reproductive processes of T. tabaci .…”
Section: Discussionmentioning
confidence: 99%